PENERAPAN MODEL DEEP LEARNING UNTUK MENINGKATKAN LITERASI EKONOMI SISWA SMA NEGERI 3 KOTA TERNATE - Nadila Rumbou; Ode Zulaeha; Arfika Jawa (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
The low level of economic literacy among high school students poses a significant challenge in developing their ability to understand economic concepts and make informed financial decisions. This study aims to analyze the implementation of the Deep Learning model in improving the economic literacy of students at SMA Negeri 3 Kota Ternate. A quasi-experimental method was employed using a non-equivalent control group design. The sample consisted of two classes: the experimental class, which applied the Deep Learning-based learning model, and the control class, which used conventional teaching methods. Data collection instruments included an economic literacy test and an observation sheet on learning activities. The results indicated a significant improvement in the economic literacy scores of students in the experimental class compared to the control group. Furthermore, students’ learning engagement increased, marked by active participation in analyzing real-life economic issues. The study concludes that implementing the Deep Learning model effectively enhances students’ economic literacy through critical, reflective, and contextual thinking processes. These findings recommend integrating the Deep Learning model into economics instruction to foster deeper and more applicable understanding among students.